APLIKASI CITRA LANDSAT DAN SIG UNTUK PEMANTAUAN GARIS PANTAI PULAU NUSA PENIDA TAHUN 1973, 1978, 1995, 2000 DAN 2013 - , NOVIANI JATININGRUM ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The shores of small island has a simple physical character. Behind the simple characteristic, they have potensial resources and threats which must be considered in their development. Because of that, shoreline monitoring need to be done to maintain of the potentials by minimizing the threat. Therefore purpose this study consist of (1) to know result of shoreline identification and mapping in Nusa Penida Island of 1973, 1995, 2000 and 2013 by using Landsat extraction, ( 2) to describe shoreline changes of Nusa Penida Island in 1973 , 1978 , 1995, 2000, and 2013 from internal and external factors of the island